EDNRA Gene rs1878406 Polymorphism is Associated With Susceptibility to Large Artery Atherosclerotic Stroke - Wei, Wan; Xuan, Xianjun; Zhu, Jiahui; Chen, Tianwen; Fang, Yudan; Ding, Jiao; Ji, Danfei; Zhou, Guoyi; Tang, Bo; He, Xudong (Frontiers in Genetics, 2022)
Objective: We performed this study to investigate whether the EDNRA gene rs1878406 C > T polymorphism is associated with risk of large artery atherosclerosis (LAA) stroke in the Chinese Han population. Methods: Genotyping of rs1878406 was performed in 1,112 LAA stroke patients and 1,192 healthy controls. Multivariate logistic regression analyses were applied to assess the effect of the rs1878406 C > T polymorphism on susceptibility to LAA stroke. Results: A significant increase of LAA stroke risk was found in the recessive model (TT vs. CC/TC, OR = 1.74, 95% CI = 1.23–2.48, p = 0.002) and co-dominant model (TC vs. CC, OR = 1.06, 95% CI = 0.89–1.27, TT vs. CC, OR = 1.79, 95% CI = 1.25–2.55, p = 0.006). However, the interaction between age and genotypes of rs1878406 was not statistically significant, and no significant interactive effect was observed between the rs1878406 C > T polymorphism and sex (p > 0.05). Conclusion: The rs1878406 C > T polymorphism is associated with increased risk of LAA stroke in the Chinese Han population.